Designing Eco-Islamic Memory Palace Media to Reduce Math Anxiety and Enhance Academic Resilience - Solihin, Annas; Mariana, Neni; Purwoko, Budi (Jurnal Kajian Bimbingan dan Konseling, 2026)
Math anxiety continues to hinder students' performance and emotional well-being in elementary mathematics education. This study aimed to develop and test the effectiveness of Eco-Islamic Memory Palace Media in reducing math anxiety and strengthening academic resilience. Employing the Plomp development model, the study involved three phases: preliminary research to identify psychological needs, prototyping of the media design, and a formative evaluation with expert validation and empirical testing on students (N = 24). The media integrated environmental imagery and Islamic values into visual-spatial mnemonic structures to create meaningful, calm, and emotionally safe learning experiences. Quantitative data analysis showed a significant decrease in students' math anxiety scores and a notable increase in resilience levels. The media was also rated highly feasible based on content validity, attractiveness, and usability. These findings demonstrate the potential of memory-based digital interventions rooted in spiritual and environmental contexts to serve as effective psychological and pedagogical tools. The study contributes to the growing body of research in positive psychology in education, highlighting the value of culturally and spiritually responsive instructional design. Implications include the need for holistic teaching approaches that address cognitive performance alongside emotional support and character development in early mathematics education.